2020
DOI: 10.1017/s0003055420000556
|View full text |Cite
|
Sign up to set email alerts
|

Does Property Ownership Lead to Participation in Local Politics? Evidence from Property Records and Meeting Minutes

Abstract: Homeowners and renters have participated in politics at different rates throughout American history, but does becoming a property owner motivate an individual to participate in local politics? I combine deed-level property records in California and Texas with an original dataset on individual comments in local city council meetings to study the role of property ownership in shaping costly forms of political behavior, and I document large inequalities in who participates at city council meetings. I also link pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…According to Fischel's theory and the abundant literature on the NIMBYism of homeowners, they act on their preferences by opposing development directly, on planning boards shaping zoning laws and specific plans (Einstein 2021), and indirectly, through participation in local elections (McGregor and Spicer 2016). Consistent with these expectations, owners tend to be more active than renters in local planning decisions; they tend to vote more than renters in local elections; and they tend to vote more when they are dissatisfied than when they are satisfied (Einstein, Glick and Palmer 2019;Holian 2011;Yoder 2020). Since the majority among voters in most cities in developed countries are owner-occupiers, Fischel's theory predicts that their interest will prevail, leading to under-development of high-demand neighborhoods and cities.…”
Section: Theoretical Background: Housing Supply Limitations Nimbyism ...mentioning
confidence: 95%
“…According to Fischel's theory and the abundant literature on the NIMBYism of homeowners, they act on their preferences by opposing development directly, on planning boards shaping zoning laws and specific plans (Einstein 2021), and indirectly, through participation in local elections (McGregor and Spicer 2016). Consistent with these expectations, owners tend to be more active than renters in local planning decisions; they tend to vote more than renters in local elections; and they tend to vote more when they are dissatisfied than when they are satisfied (Einstein, Glick and Palmer 2019;Holian 2011;Yoder 2020). Since the majority among voters in most cities in developed countries are owner-occupiers, Fischel's theory predicts that their interest will prevail, leading to under-development of high-demand neighborhoods and cities.…”
Section: Theoretical Background: Housing Supply Limitations Nimbyism ...mentioning
confidence: 95%
“…A recent explosion of datasets in the social sciences has led to unprecedented, large-scale study of U.S. politics, elections, and policy-making at the national [5][6][7][8] and state levels 9,10 . Meanwhile, most contemporary studies of local policy-making rely primarily on case studies or small sets of individual places 11,12 , lab experiments 13 , or have required extensive (and expensive) manual data collection [14][15][16][17] .…”
Section: Background and Summarymentioning
confidence: 99%
“…Concerning housing policies, findings are fairly consistent regarding the effects on political engagement, but findings regarding voter choice and incumbent support are mixed. In the US context, homeowners turn out at higher rates in local elections and property owners are more likely to participate in local council meetings and donate during elections (Yoder 2020). Kumar (2022), on examining a housing lottery in India, found that becoming a homeowner increased local non-electoral mobilization.…”
Section: Beneficiaries and The Electoratementioning
confidence: 99%